2009
DOI: 10.1007/s00330-008-1268-3
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse optical tomography of the breast: preliminary findings of a new prototype and comparison with magnetic resonance imaging

Abstract: This paper presents an evaluation of a prototype diffuse optical tomography (DOT) system. Seventeen women with 18 breast lesions (10 invasive carcinomas, 2 fibroadenomas, and 6 benign cysts; diameters 13-54 mm) were evaluated with DOT and magnetic resonance imaging (MRI). A substantial fraction of the original 36 recruited patients could not be examined using this prototype due to technical problems. A region of interest (ROI) was drawn at the lesion position as derived from MRI and at the mirror image site in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…[10][11][12][13][14] Most DOT breast imaging systems used fibers to deliver lasers to breast surface and collected the diffused light on the breast surface, in which the measurement number was determined by the optode pairings. 11,[15][16][17][18][19][20][21][22] To increase the number of measurement data, Culver et al reported a charge coupled device (CCD) camera based DOT imaging system. 23 Turner et al used a CCD camera to measure early photons in a DOT imaging system.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] Most DOT breast imaging systems used fibers to deliver lasers to breast surface and collected the diffused light on the breast surface, in which the measurement number was determined by the optode pairings. 11,[15][16][17][18][19][20][21][22] To increase the number of measurement data, Culver et al reported a charge coupled device (CCD) camera based DOT imaging system. 23 Turner et al used a CCD camera to measure early photons in a DOT imaging system.…”
Section: Introductionmentioning
confidence: 99%
“…Since the three primary weak absorbers, water and both oxygenated and deoxygenated hemoglobin inside tissue have different absorption properties, the DOT offers the opportunity to distinguish different biological tissues [2]. The most current significant applications of DOT are breast cancer diagnostics [3,4], joint imaging [5] and blood oximetry in human muscle and brain tissue [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…10 Many research groups have made significant advances in the field of DOT breast imaging, employing a variety of designs for instrumentation. [11][12][13][14][15][16][17][18] Time-domain (TD) systems inject a short light pulse (full-width-half-maximum typically less than 0.1 ns) into the breast and measure the time-dependent transmitted intensities. These systems provide a wealth of information about the optical properties of the tissue, however, data acquisition typically takes three to five minutes and the systems are comparably expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have made successful use of CW instrumentation for breast cancer detection including Liang et al who showed sensitivity and specificity of 82 and 71% in 33 patients 17 and van de Ven et al who showed detection rates of 60 to 80% in 17 patients. 18 In addition to these three classes of optical tomography imaging systems (TD, FD, and CW), a number of promising hybrid systems have been developed that combine DOT with other imaging modalities such as x-ray mammography, 20 ultrasound, 21,22 and MRI. 23,24 Regardless of the type of instrumentation, all DOT systems rely on endogenous contrast generated by the physiology of tissue, either in steady state or after perturbing the state of the physiology in order to generate a transient response to differentiate between healthy and cancerous tissue.…”
Section: Introductionmentioning
confidence: 99%